A study for system design that guarantees the integrity of computer files based on blockchain and checksum - Minyoung Kim (International Journal of Advanced Culture Technology(IJACT), 2021)
When a data file is shared through various methods on the Internet, the data file may be damaged in various cases. To prevent this, some websites provide the checksum value of the download target file in text data type. The checksum value provided in this way is then compared with the checksum value of the downloaded file and the published checksum value. If they are the same, the file is regarded as the same. However, the checksum value provided in text form is easily tampered with by an attacker. Because of this, if the correct checksum cannot be verified, the reliability and integrity of the data file cannot be ensured. In this paper, a checksum value is generated to ensure the integrity and reliability of a data file, and this value and related file information are stored in the blockchain. After that, we will introduce the research contents for designing and implementing a system that provides a function to share the checksum value stored in the block chain and compare it with other people's files.